A reproductive, developmental and neurobehavioral study following oral exposure of tetrabromobisphenol A on Sprague-Dawley rats. (2nd March 2015) - Cope, Rhian B.; Kacew, Sam; Dourson, Michael
Abstract: The objectives of these GLP US EPA OPPTS 970.3800 and 970.3700 studies were to examine the effects of tetrabromobisphenol A (TBBPA) at oral doses of 10, 100 or 1000 mg/kg BW/day over the course of 2 generations on growth as well as behavioral, neurological and neuropathologic functions in offspring. In a separate study the influence of oral TBBPA (0, 100, 300 or 1000 mg/kg BW/d) was examined on embryonic/fetal development from gestation days (GDs) 0–19. In the reproductive study, exposure to ≥100-mg/kg BW/d TBBPA resulted in a decrease in circulating, peripheral thyroxine (T4 ) levels in rats that were not accompanied by any marked alterations in triiodothyronine (T3 ) and thyroid stimulating hormone (TSH). These findings are explainable on the basis of induction of rat liver catabolism, a phenomenon that may be species-specific and not relevant for humans. TBBPA at up to 1000 mg/kg BW/d was not associated with any significant non-neurological effects on reproduction, growth and development. A subtle reduction, of unknown biological relevance, in the thickness of the parietal cortices of 11-day-old F2 pups in the 1000 mg/kg BW/d group was noted. This change was not accompanied by evidence of micro-anatomic changes. No estrogenic effects sufficient to affect macro and micro anatomy, fertility, reproduction, development, survival or behavior were detected in the embryofetal development study or in the multigenerational study. No other TBBPA-related effects on developmental neurotoxicity/neuropathology were detected. In the developmental study no TBBPA related change in mortality rate was observed in any of the dams. No other significant test article-related effects were noted. The no observed effect level (NOEL) for maternal and developmental toxicity was 1000 mg/kg BW/d, the highest dose evaluated.